Hybrid function of light fraction patchouli oil in hair care formulations for effective hair and anti-dandruff treatment - Isnaini, Nadia; Muhammad, Syaifullah; Prajaputra, Vicky; Indra, Indra; Sufriadi, Elly; Ernawati, Ernawati; Riski, Cantika D. (Narra Sains Indonesia, 2025)
Hair issues, such as hair loss and dandruff, pose significant challenges in hair care. Patchouli oil, rich in bioactive components, has emerged as a promising candidate for addressing these concerns. The aim of this study was to investigate the hybrid functionality of fractionated patchouli oil in hair care formulations designed to promote hair growth and control dandruff caused by Malassezia globosa. Crude patchouli oil (CPO) was fractionated to enhance its efficacy, producing light fraction patchouli oil (LFPO), which was then characterized using gas chromatography-mass spectrometry (GC-MS) analysis. Hair tonic formulations containing three different LFPO concentrations (0.5%, 1.0%, and 1.5%) were developed and evaluated for stability, pH, viscosity, and antifungal activity against M. globosa. The results showed that LFPO contained 2.51% acid number, 0.70% ester number, 0.71 mg/kg iron content, and 25.88% patchoulol. The formulations exhibited stable physicochemical properties, with pH levels of 5.36–5.51 and viscosity ranging from 3.94 to 4.08 centipoise (cP), suitable for hair tonic applications. Formulation of 1.5% LFPO demonstrated the strongest antifungal activity, producing a 31.18±1.37 mm inhibition zone against M. globosa, surpassing ketoconazole (21.72±0.28 mm), suggesting potential as a natural antifungal agent. Histological analysis in rabbits revealed that 1.5% LFPO formulation reduced epidermal cell shedding, increased hair length by 41.6±0.35 mm after six weeks, and promoted dense hair follicle growth. This research provides a foundation for developing natural, effective, and stable hair care formulations. Despite these promising results, the efficacy and safety of LFPO formulations in humans remain unexplored. Therefore, a clinical human trial is necessary to assess skin tolerance, irritation risks, and long-term effects under real-world conditions.